Grand convergence in wound healing - The imperative for collaboration in research, innovation and quality improvement. Issue 1 (February 2018) - Samuriwo, Ray
Highlights: Grand convergence to improve population health can only be achieved through collaboration. There is an increasing amount of collaboration in wound care in the UK and Europe. It is vital to make the most of the opportunities for collaboration in wound care.